2019
DOI: 10.3390/cells8050444
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Apigenin-Biosynthesized Ultra-Small Platinum Nanoparticles on the Human Monocytic THP-1 Cell Line

Abstract: Generally, platinum nanoparticles (PtNPs) are considered non-toxic; however, toxicity depends on the size, dose, and physico-chemical properties of materials. Owing to unique physico-chemical properties, PtNPs have emerged as a material of interest for several biomedical applications, particularly therapeutics. The adverse effect of PtNPs on the human monocytic cell line (THP-1) is not well-established and remains elusive. Exposure to PtNPs may trigger oxidative stress and eventually lead to inflammation. To f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 99 publications
(119 reference statements)
4
95
0
Order By: Relevance
“…The same trend was observed in all other antioxidants, including TRX, CAT, SOD, GPx, and GST ( Figure 7B-F). Similarly, PtNPs also decreased antioxidant levels in several types of cancer cells, including SH-SY5Y cells [70], human monocytic THP-1 [71], and OS epithelial cells. In mammals, glutathione (GSH) is the dominant low-molecular-weight antioxidant.…”
Section: Effect Of Pdnps + Mlt On Antioxidant Marker Levelsmentioning
confidence: 92%
See 2 more Smart Citations
“…The same trend was observed in all other antioxidants, including TRX, CAT, SOD, GPx, and GST ( Figure 7B-F). Similarly, PtNPs also decreased antioxidant levels in several types of cancer cells, including SH-SY5Y cells [70], human monocytic THP-1 [71], and OS epithelial cells. In mammals, glutathione (GSH) is the dominant low-molecular-weight antioxidant.…”
Section: Effect Of Pdnps + Mlt On Antioxidant Marker Levelsmentioning
confidence: 92%
“…Zhao et al [82] reported that titanium dioxide nanoparticles induced mitochondrial dynamic imbalance in HT22 cells, eventually causing mitochondrial dysfunctions and decreased level of ATP synthesis. Previous studies have shown that platinum nanoparticles decreased ATP synthesis in human THP-1 [71], prostate cancer cells [70], and osteosarcoma cells. Increased level of ROS reduced the oxidative capacity by altering the oxidative phosphorylation (OXPHOS), and decreased ATP production [83].…”
Section: Pdnps + Mlt Caused Mitochondrial Dysfunctionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Synthesized NPs revealed potent anticancer activity against a human breast cancer cell line [100]. Similarly, biologically synthesized PtNPs exhibited potential cytotoxicity against various human cells such as human monocytic cells and human bone OS epithelial cells [101,102]. All these data provided strong evidence for the synthesis of PtNPs using natural products and its potential anticancer activity.…”
Section: Synthesis Of Platinum Nanoparticles Using Purified Plant Commentioning
confidence: 65%
“…In vitro data suggest that PtNCP beads inhibited cell viability of HSC-3-M3 cells in a dose-dependent manner and induced cytotoxicity with increased leakage of lactate dehydrogenase [220]. Recently, Gurunathan et al [101] reported that apigenin functionalized PtNPs exhibited potential cytotoxicity, genotoxicity, and proinflammatory responses in human monocytic cell line (THP-1) by increasing the levels of lactate dehydrogenase, generation of ROS, and production of malondialdehyde, nitric oxide, and carbonylated proteins and also increased apoptosis and oxidative DNA damage. Finally, PtNPs increased the expression of various proinflammatory cytokines such as interleukin-1β (IL-1β), IL-6, IL-8, tumor necrosis factor-α (TNF-α), granulocyte-macrophage colony-stimulating factor (GM-CSF), and monocyte chemoattractant protein 1 (MCP-1).…”
Section: Cytotoxicity Of Ptnps In Cancer and Non-cancer Cellsmentioning
confidence: 99%